Natural convection of a nanofluid in C-shaped enclosures - BENLEHBIB Afif Bouziane; Lokbaichi, Oussama; Gharnaout, Badia (Université Amar Telidji- Laghouat FACULTE : TECHNOLOGIE Département de génie mécanique, 2023)
In this thesis a numerical study has been carried out on the problem of natural convection and heat transfer using nanofluid (Cu-Water (H2O)) and (TiO2-Water (H2O)) which is the mixture between water and nanoparticles in a c-shaped enclosure. Our problem was defined for a type of geometry (a c-shaped enclosure with different (AR = 0.2,0.4,0.6,0.8) aspect ratio, the flow is generated by heat transfer by free (natural) convection. In our simulation we used four concentrations of nanoparticles, for each concentration the Rayleigh number varied between 103 and 106. The results obtained for different Rayleigh numbers (Ra =103, Ra =104, Ra=105, Ra =106) show an increase in average Nusselt due to the increase in volume fraction. For all volume fractions (φ =0, φ =0.03, φ =0.06, φ =0.1), the increase in average Nusselt number is due to the increase in Rayleigh number. Taking into consideration these results the improvement of flow efficiency and heat transfer efficiency is related to the variation of Rayleigh number with volume fraction.
Option : Energetics